Media convergence and participatory culture: The possibility of new relationships between social agents in the field of communication and new technologies - Camargo, Aline Cristina [UNESP]; Vieira Miranda, Giovani [UNESP]; Magnoni, Antonio Francisco [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2019)
This article analyzes the collaborative publishing of two Internet portals, G1 and A Tarde/uol, in order to identify the change in the position of social agents in the field of communication with the advent of new technologies and in the context of mobile devices usage. In order to perform the analyzes, the concepts of Castells (1996), Jenkins (2009) and Bourdieu (2004, 2008) were used, and the methodology of content analysis (ca) was applied using qualitative methods of corpus analysis. The results show that there is a change in the position of social agents in the communication area, from consumers to producers, from passive to active, from isolated to connected.
Convergencia mediática y cultura participativa: La posibilidad de nuevas relaciones entre los agentes sociales en el campo de la comunicación y las nuevas tecnologías
Convergência midiática e cultura participativa: A possibilidade de novas relaÇÕes entre os agentes sociais no campo da comunicaÇÃo e as novas tecnologias
Keywords: Communication area; Content analysis; Media convergence; Mobile devices; Participatory culture